Molecular cooling in the diffuse interstellar medium - Glover, Simon; Clark, Paul C. (Monthly notices of the Royal Astronomical Society, 2014)
We use a simple one-zone model of the thermal and chemical evolution of interstellar gas to study whether molecular hydrogen (H2) is ever an important coolant of the warm, diffuse interstellar medium (ISM).We demonstrate that at solar metallicity, H2 cooling is unimportant and the thermal evolution of the ISM is dominated by metal-line cooling.
In original form 2013 May 31
Gesehen am 05.10.2020